EFL Teachers’ Belief about Spoken Corrective Feedback and Their Classroom Practice - Surya Rifqi (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2019)
The purposes of this study are to investigate ELT teachers’ beliefs about spoken corrective feedback, the educational factors affecting teachers’ beliefs, the link between teachers’ stated beliefs about spoken corrective feedback and their classroom practice. The data were collected through interview with the subjects, observation checklist, audio recording, and field notes. The finding of this study shows that the existence of corrective feedback helped the students to gain infomations to do the reflection and activate their awareness of what they said and did. The differences of what to correct, when to correct, and how to correct students’ errors between lecturers could be understood because the lecturers hold different focus of courses, different decisions, adaptation to the effective corrective feedback strategies